Analisis Kualitas Audit Pada Masa Covid-19 - sapdian, asep; Widia Astuti; Fharas Syawalia (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the quality of company audits during the Covid 19 Pandemic with the literature review method. The results found that the impact of the Covid-19 pandemic on audit quality was caused by cutting audit costs, in addition to the implementation of remote auditing which caused a lot of unreliable evidence. It was also found that the level of audit delay increased, which could allow manipulation of financial statements